SKping cell cycle regulation: role of ubiquitin ligase SKP2 in hematological malignancies - William, Jonahunnatha Nesson George; Dhar, Ruby; Gundamaraju, Rohit; Sahoo, Om Saswat; Pethusamy, Karthikeyan; Raj, A. F. P. Allwin Mabes; Ramasamy, Subbiah; Alqahtani, Mohammed S.; Abbas, Mohamed; Karmakar, Subhradip (Frontiers in Oncology, 2024)
Hypoxia-inducible factor 12. IFN-γ-Interferon-gamma 13. TCGA-The Cancer Genome Atlas 14. BRCA1-Monoclonal antibody 15. MDSC-Myeloid-derived suppressor cells 16. BRCR-ABL -The breakpoint cluster region protein also known as renal carcinoma antigen NY-REN-26 17. mTORC-Mammalian Target of Rapamycin Complex 18. MAPK-Mitogen-activated protein Kinase 19. CUL1-Cullin1 20. JAK -Janus kinase 21. TAM-Tumor-associated macrophages 22. TAN-Tumor-associated neutrophils 23. TET-Ten-eleven translocation proteins 24. TGF β-Transforming growth factor β 31 25. TNBC-Triple-negative breast cancer 32 26. TNF α-Tumor necrosis factor α 33